Idiopathic AA amyloidosis presenting with initial abdominal pain: a case report and literature review - Pianpian Xia; Pianpian Xia; Pianpian Xia; Deliang Liu; Deliang Liu; Deliang Liu; Feihong Deng; Feihong Deng; Feihong Deng; Dalian Ou; Dalian Ou; Dalian Ou; et al. (Frontiers in Medicine)
Amyloidosis is a rare disease, often secondary to chronic inflammation or autoimmune disorders, with an unclear etiology in some cases. Herein, we report a 67-year-old male patient presenting with recurrent abdominal pain and multi-system involvement. The diagnosis of AA amyloidosis was confirmed by Congo red staining of small intestinal mucosal and bone marrow biopsies. Despite comprehensive screening, no definite etiology was identified. This case highlights that amyloidosis should be considered in patients with unexplained abdominal pain and multisystem abnormalities, and early tissue biopsy is crucial for diagnosis.